Anterior Epistaxis in a Patient with a History of Allergic Rhinitis: A Case Report - Marlina, Lina; Hendrika, Wendy; Rizki, Muhammad (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Epistaxis or nosebleed is one of the emergency conditions in the field of otorhinolaryngology that is often encountered, especially anterior epistaxis. Allergic rhinitis can be a predisposing factor for epistaxis due to chronic inflammation of the nasal mucosa that causes fragility of blood vessels in the Kiesselbach plexus area. Objective: To report a case of anterior epistaxis in a patient with a history of allergic rhinitis, and to evaluate the appropriateness of the diagnosis and management based on existing theories and literature. Methods: This writing is a descriptive case report of a patient who came with complaints of nosebleeds. Anamnesis, physical examination, and supporting examinations were performed to confirm the diagnosis and formulate management. Results and Discussion: The patient was diagnosed with anterior epistaxis triggered by the underlying condition of allergic rhinitis. Therapy given was in the form of local treatment (cauterization) and antihistamine medication to control allergic symptoms. The evaluation results showed significant clinical improvement without recurrence. Conclusion: Anterior epistaxis can occur as a complication of chronic allergic rhinitis. The diagnosis established through anamnesis, physical examination, and supporting tests is consistent with the theory outlined in the literature review. Appropriate treatment of underlying causes, such as allergic rhinitis, is crucial to prevent recurrence.